2018
DOI: 10.1080/02673037.2018.1509949
|View full text |Cite
|
Sign up to set email alerts
|

Family formation, parental background and young adults’ first entry into homeownership in Britain and Germany

Abstract: Although previous research shows that family dynamics and parental socioeconomic status influence the timing of young adults' first entry into homeownership, much less is known about how the role of family factors may vary across countries with different housing systems. In this article, we use panel survey data from Britain and Germany to compare how family life course careers and parental socioeconomic background influence young adults' initial entry into homeownership in these two divergent national context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 58 publications
1
42
0
Order By: Relevance
“…Individual characteristics that have been found to exert an influence on the likelihood of first‐time homeownership are related to the respondent's socioeconomic status and that of their spouse. A positive influence was found for higher education (Mulder & Wagner, ) but not so in a newer study for Germany (Bayrakdar et al, ), occupational prestige (Mulder & Wagner, ), employment or occupational status (Enström Öst, ; Kurz, ; Lersch & Luijkx, ), and income (Bayrakdar et al, ; Enström Öst, ), whereas not being in employment (Coulter, ; Mulder & Wagner, ) or being unemployed (Bayrakdar et al, ; Kurz, ) were found to decrease the likelihood of moving to a self‐owned home. Moreover, living with a partner or spouse was found to increase the likelihood of becoming a homeowner (Coulter, ; Enström Öst, ).…”
Section: Theoretical Framework and State Of Researchmentioning
confidence: 94%
See 4 more Smart Citations
“…Individual characteristics that have been found to exert an influence on the likelihood of first‐time homeownership are related to the respondent's socioeconomic status and that of their spouse. A positive influence was found for higher education (Mulder & Wagner, ) but not so in a newer study for Germany (Bayrakdar et al, ), occupational prestige (Mulder & Wagner, ), employment or occupational status (Enström Öst, ; Kurz, ; Lersch & Luijkx, ), and income (Bayrakdar et al, ; Enström Öst, ), whereas not being in employment (Coulter, ; Mulder & Wagner, ) or being unemployed (Bayrakdar et al, ; Kurz, ) were found to decrease the likelihood of moving to a self‐owned home. Moreover, living with a partner or spouse was found to increase the likelihood of becoming a homeowner (Coulter, ; Enström Öst, ).…”
Section: Theoretical Framework and State Of Researchmentioning
confidence: 94%
“…Parental homeownership was found to accelerate young adults' entry into homeownership in various contexts (Bayrakdar et al, ; Coulter, ; Kurz, ; Lersch & Luijkx, ; Mulder, Dewilde, van Duijn, & Smits, ; Mulder & Wagner, ), whereas other parental characteristics like education (Mulder & Wagner, ), single parenthood or step‐parenthood, and number of siblings (Bayrakdar et al, ; Lersch & Luijkx, ) were barely influential. There is evidence that the parents of home buyers are involved in an increasing number of property transactions in European countries (Ronald & Lennartz, ) and that the influence of parental tenure on the transition into homeownership has increased (Coulter, ; Kurz, ), especially in expensive housing markets (Mulder et al, ).…”
Section: Theoretical Framework and State Of Researchmentioning
confidence: 99%
See 3 more Smart Citations